2007
DOI: 10.1039/b617043a
|View full text |Cite
|
Sign up to set email alerts
|

Visible light inactivation of bacteria and fungi by modified titanium dioxide

Abstract: Visible light induced photocatalytic inactivation of bacteria (Escherichia coli, Staphylococcus aureus, Enterococcus faecalis) and fungi (Candida albicans, Aspergillus niger) was tested. Carbon-doped titanium dioxide and TiO2 modified with platinum(IV) chloride complexes were used as suspension or immobilised at the surface of plastic plates. A biocidal effect was observed under visible light irradiation in the case of E. coli in the presence of both photocatalysts. The platinum(IV) modified titania exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(142 citation statements)
references
References 35 publications
7
134
1
Order By: Relevance
“…Due to C. crustacea did not grow on paint-coated MEA under both dark and light exposure conditions, the species was excluded from this list. The results have confirmed the findings by Maneerat and Hayata 21 and Mitoraj et al 34 ; concerning the inhibition effect of TiO 2 -mediated photocatalysis on fungal growth. Chen et al 25 also found that photocatalytic disinfection processes were effective in the A. niger growth inhibition only under UVA irradiation.…”
Section: Resultssupporting
confidence: 82%
“…Due to C. crustacea did not grow on paint-coated MEA under both dark and light exposure conditions, the species was excluded from this list. The results have confirmed the findings by Maneerat and Hayata 21 and Mitoraj et al 34 ; concerning the inhibition effect of TiO 2 -mediated photocatalysis on fungal growth. Chen et al 25 also found that photocatalytic disinfection processes were effective in the A. niger growth inhibition only under UVA irradiation.…”
Section: Resultssupporting
confidence: 82%
“…After another 30-day operation, the PC reactor still maintained high disinfection ability to all biohazards with only very slightly decrease of inactivation efficiencies of bacteria and molds. In addition, it must be noted that, usually, molds were more difficult to be inactivated than bacteria with equal concentrations by PC treatment because molds are eucaryotic organisms surrounded by a rigid cell wall, and mold cell is much larger than that of bacteria [40,41]. Nevertheless, PC inactivation efficiency of molds was slightly higher than that of bacteria on day 30 in this work.…”
Section: Removal Of Biohazards By Photocatalytic Technologymentioning
confidence: 63%
“…8-9 logreduction/0.5 h) can be compared with water suspensions of TiO 2 promoted with Pt(IV) salts (ca. 6 log-reduction/0.5 h) [43]; TiO 2 supported on EVOH (6.3 log-reduction/0.5 h) [7a] or TiO 2 -Ni contains (2 log-reduction for extended period of times) [44]. Other biocides based on simple chemicals as trichlorosan on styrene-acetate copolymers (initial rate enhancement below 2 with respect to the polymer alone) [45]; organometallic complexes leading to oxygen radical formation (3.5 log-reduction/4 h) [46]; or UV-treated Nylon (1.8 log-reduction/6 h) [47] provide further support to our conclusion concerning the good performance of the nanocomposite films here described.…”
Section: Resultsmentioning
confidence: 99%